Pelaksanaan Metode Bermain Peran Dalam Meningkatkan Kemampuan Sosial Pada Anak Usia Dini - Endang Kurnia; Asnawati Asnawati; Ranny Fitria Imran (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the implementation of the role-playing method in enhancing the social skills of early childhood children. The social skills in question include social interaction, cooperation, adherence to rules, empathy and caring, and social independence. The study was conducted at PAUD Kembang Ayun in Central Bengkulu Regency using a qualitative approach. Data collection involved observation and interviews with teachers and the school principal as key informants. The results indicate that the implementation of the role-playing method positively impacts the development of children's social skills. Through role-playing activities, children become more active in interacting with peers, capable of cooperating in groups, and better at understanding the rules governing shared activities. Furthermore, children begin to demonstrate empathy and caring—such as helping friends, sharing, and responding to others' feelings. This method also helps boost children's self-confidence and independence in expressing opinions and assuming roles during activities. However, the implementation of the role-playing method still requires guidance and support from teachers, particularly for children who lack confidence or are not yet actively participating. Therefore, careful planning, the selection of appropriate themes, and consistent practice are essential for the role-playing method to be optimally applied in enhancing the social skills of early childhood children.